Effect of a resin-modified glass-ionomer with calcium on enamel demineralization inhibition: an in vitro study - Cassiana Koch SCOTTI; Marilia Mattar de Amoêdo Campos VELO; Nair Cristina Margarido BRONDINO; Bruno Martini GUIMARÃES; Adilson Yoshio FURUSE; Rafael Francisco Lia MONDELLI; Juliana Fraga Soares BOMBONATTI (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract We assessed the effect of a new coating material based on resin-modified glass-ionomer with calcium (Ca) in inhibiting the demineralization of underlying and adjacent areas surrounding caries-like lesions in enamel. The measures used were surface hardness (SH) and cross-sectional hardness (CSH). Thirty-six bovine enamel specimens (3 × 6 × 2 mm) were randomly allocated into three groups (n = 12): No treatment (NT); resin-modified glass-ionomer with Ca (Clinpro XT Varnish, 3M ESPE) (CL), and fluoride varnish (Duraphat, Colgate) (DU). The specimens were subjected to alternated immersions in demineralizing (6 h) and remineralizing solutions (18 h) for 7 days. SH measurements were conducted at standard distances of 150, 300, and 450 µm from the treatment area. CSH evaluated the mean hardness profile over the depth of the enamel surface and at standard distances from the materials. The energy-dispersive X-ray spectroscopy analysis was conducted to evaluate the demineralization bands created on the sublayer by % of calcium (Ca), phosphorus (P), and fluoride (F). Ca/P weight ratio was also calculated. Based on SH and CSH measurements, there was no difference between groups at the distances 150 µm (p = 0.882), 300 µm (p = 0.995), and 450 µm (p = 0.998). Up to 50 µm depth (at 150 µm from the treatment area), CL showed better performance than DU ( p< 0.05). NT presented higher loss of Ca and P than CL and DU (p < 0.05). There was no significant difference in the % of F ion among the three groups. The new coating material was similar to F varnish in attenuating enamel demineralization.